2013
DOI: 10.2477/jccj.2012-0017
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Computational Chemistry to Designing Materials and Microstructure in Fuel Cell Technologies

Abstract: Our recent applications of computational chemistry methods to practical issues in fuel cell technologies are reviewed in the manuscript; i.e., degradation of polymer electrolyte and platinum catalyst in a polymer electrolyte fuel cell (PEFC), development of platinum alternative catalyst for low temperature fuel cells, sulfur poisoning and microstructure optimization of solid oxide fuel cell anode. As degradation issues in PEFC, degradation mechanisms of polymer electrolyte from side chain and platinum dissolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Hydrogen and carbon monoxide derived from hydrocarbons are the typical fuel of SOFC. The understanding of oxidation reactions from these fuels is one of the focuses of anode research for the material design of high catalytic activity [2][3][4][5][6][7][8][9]. Ni-yttria-stabilized zirconia (Ni-YSZ) is the most widely used anode material for current SOFC.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen and carbon monoxide derived from hydrocarbons are the typical fuel of SOFC. The understanding of oxidation reactions from these fuels is one of the focuses of anode research for the material design of high catalytic activity [2][3][4][5][6][7][8][9]. Ni-yttria-stabilized zirconia (Ni-YSZ) is the most widely used anode material for current SOFC.…”
Section: Introductionmentioning
confidence: 99%
“…Group IV–VI semiconductor compounds represent an interesting field of study not only for a variety of technological applications but also from the theoretical point of view. These IV–VI semiconductor families have been extensively studied over the past decades due to their tunable properties, which is of particular interest. , In this sense, theoretical data are necessary for predicting size, shape, and stability of the group IV–VI semiconductor compounds. …”
Section: Introductionmentioning
confidence: 99%
“…The initial study reported here did not find Pt(OH) or Pt(OH) 2 to have a strong effect on the structure of nC 31 (e.g., Figure 6g). Pt 4+ (H 2 O) 2 (OH) 4 , appears to be more effective and was selected for the ab initio calculations on the basis of a low desorption energy, thermodynamic stability, and the ability to dissolve platinum nanoparticles [46], a situation compatible with the platinum assays for the Freetown studies.…”
Section: Discussionmentioning
confidence: 99%